Análise crítica das metodologias de avaliação de temperatura e umidade em câmeras climáticas e térmicas - Brionizio, Júlio Dutra (2007)
Climatic and thermostatic chambers are equipment widely used in many industrial fields e research institutes in order to simulate certain environmental conditions. In many cases, it is extreme important that the measurements carried out in these equipment be reliable, once inadequate measurements can lead to equivocal conclusions about the tests performed. So, the calibration of the chamber is essential to guarantee the confidentiality of the results of the simulated conditions and to allow the user to get knowledge of the performance and metrological characteristics of the equipment. This dissertation presents a study of three calibration/characterisation methods of chamber from three different countries. This work exhibits the problem, analyses several aspects of the documents, speaks about hygrometry and thermometry, shows a case study and makes considerations about the subject